Infant Formula Feeding Changes the Proliferative Status in Piglet Neonatal Mammary Glands Independently of Estrogen Signaling. Issue 4 (5th November 2019) - Mercer, Kelly E; Bhattacharyya, Sudeepa; Sharma, Neha; Chaudhury, Mousumi; Lin, Haixia; Yeruva, Laxmi; Ronis, Martin J
ABSTRACT: Background: Soy infant formula contains isoflavones, which are able to bind to and activate estrogen receptor (ER) pathways. The mammary gland is sensitive to estrogens, raising concern that the use of soy formulas may promote premature development. Objective: We aimed to determine if soy formula feeding increases mammary gland proliferation and differentiation in comparison to other infant postnatal diets. Methods: White-Dutch Landrace piglets aged 2 d received either sow milk (Sow), or were provided milk formula (Milk), soy formula (Soy), milk formula supplemented with 17-beta-estradiol (2 mg/(kg·d); M + E2), or milk formula supplemented with genistein (84 mg/L of diet; M + G) until day 21. Mammary gland proliferation and differentiation was assessed by histology, and real-time RT-PCR confirmation of differentially expressed genes identified by microarray analysis. Results: Mammary terminal end bud numbers were 19–31% greater in the Milk, Soy, and M + G groups relative to the Sow and M + E2, P <0.05. Microarray analysis identified differentially expressed genes between each formula-fed group relative to the Sow (±1.7-fold, P <0.05). Real-time RT-PCR confirmed 2- to 4-fold increases in mRNA transcripts of genes involved in cell proliferation, insulin-like growth factor 1 ( IGF1 ), fibroblast growth factor 10 ( FGF10 ), and fibroblast growth factor 18 ( FGF18 ), in all groups relative to the Sow, P <0.05. In contrast, genes involved in cell differentiation and ductal morphogenesis, angiotensin II receptor type 2 ( AGTR2 ), microtubule associated protein 1b ( MAP1B ), and kinesin family member 26b ( KIF26B), were significantly upregulated by 2-, 4-, and 13-fold, respectively, in the M + E2 group. Additionally, mRNA expression of ER-specific gene targets, progesterone receptor ( PGR ), was increased by 12-fold, and amphiregulin ( AREG ) and Ras-like estrogen regulated growth inhibitor ( RERG ) expression by 1.5-fold in the M + E2 group, P <0.05. In the soy and M + G groups, mRNA expressions of fatty acid synthesis genes were increased 2- to 4-fold. Conclusions: Our data indicate soy formula feeding does not promote ER-signaling in the piglet mammary gland. Infant formula feeding (milk- or soy-based) may initiate proliferative pathways independently of estrogenic signaling.